Penilaian Kinerja dan Investasi dengan Menggunakan Balanced Scorecard - Kusumawati Yupie (Semantik, 2011)
Balanced score card is contemporary managemen tools used to help the organization capacity doubel the company finance achievement. Since the company is basically considered as wealth-creator institution, so the use of balanced score card within the company management is promising to give a significant improvement to create company wealth.Keyword: Penilaian kerja, balanced scorecard, contemporary management tools